Biopharmaceuticals: Reference Products and Biosimilars to Treat Inflammatory Diseases. Issue 4 (August 2017) - Gils, Ann; Bertolotto, Antonio; Mulleman, Denis; Bejan-Angoulvant, Theodora; Declerck, Paul J.
Abstract : Abstract: Biopharmaceuticals are primarily therapeutic proteins developed to perform specific functions by acting on the disease pathophysiology. Compared with low-molecular chemically synthesized drugs, production of biopharmaceuticals is much more complex and routes of administration and pharmacokinetics differ. Biopharmaceuticals are blockbusters in the treatment of inflammatory diseases, such as psoriasis, multiple sclerosis, rheumatic diseases, and inflammatory bowel diseases, and the introduction of these drugs has revolutionized treatment. Disadvantages include their high costs and the fact that they can evoke antidrug antibodies leading to decreased efficacy. Treatment can be optimized through the development of dosing algorithms and cost can be reduced by biosimilars, after a comparable biological activity, safety, and efficacy have been demonstrated.